2009
DOI: 10.1002/app.29482
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion behavior of water and sulfuric acid in epoxy/organoclay nanocomposites

Abstract: ABSTRACT:The research on polymer-layered silicate nanocomposites is currently an expanding field of study because they often exhibit a wide range of improved properties over their unmodified starting polymers. Epoxy/ organoclay nanocomposites have been prepared by intercalating epoxy into the organoclay montmorillonite. The intercalation and/or exfoliation of the clay within the nanocomposite were monitored using X-ray diffraction and transmission electron microscopy. Diffusion was studied through epoxy sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…In the initial stage of the absorption, up to approximately M t /M ∞ = 0.5 the increase in mass shows a linear relationship with the square root of time [26][27][28]. As observed, the plot of M t /M ∞ vs. t 1/2 /2l is linear at the initial stage and the diffusivity can be calculated from its slope, hence, the diffusion behavior of water may be considered to follow the Fickian type diffusion.…”
Section: Diffusion Behavior Of Water In Pa6/organoclay Nanocompositessupporting
confidence: 53%
“…In the initial stage of the absorption, up to approximately M t /M ∞ = 0.5 the increase in mass shows a linear relationship with the square root of time [26][27][28]. As observed, the plot of M t /M ∞ vs. t 1/2 /2l is linear at the initial stage and the diffusivity can be calculated from its slope, hence, the diffusion behavior of water may be considered to follow the Fickian type diffusion.…”
Section: Diffusion Behavior Of Water In Pa6/organoclay Nanocompositessupporting
confidence: 53%
“…In some reports, it is shown that due to clay incorporation water absorption is decreased, due to increased barrier effects [10,11]. In other literatures, water absorption is shown to increase due to hydrophilicity of clays [12,13]. Crystallinity of polymers is another important participating factor in controlling water absorption properties of polymeric materials.…”
Section: Introductionmentioning
confidence: 96%
“…There are some literatures on water absorption of polymer/clay nanocomposites, but they are not crosslinked [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Moisture absorption behavior and laminate degradation of BMI resin has been addressed occasionally in varying detail [2,[6][7] but not as extensively investigated as fiber-reinforced epoxy laminates [1,[3][4][5][8][9][10][11]. In this paper, the effect of process induced voids on moisture absorption kinetics of HexPly® F650, a bismaleimide (BMI) resin reinforced with 581 style, eight-harness satin weave quartz fabric is investigated.…”
Section: Introductionmentioning
confidence: 99%